733 PTSD and Sleep Disorders in Medical Learners and Healthcare Providers. (3rd May 2021) - Tinsley, Meagan; Hunt, Grace; Alvarez, Mark; Gremillion, Rachel; Jumonville, Allison; Ghaffar, Yahya; Champagne, Kristin; Derouen, Alyssa; Knox, Brianne; Bokun, Kevin; Allen, Mariah; Ninh, Michael; et al.
Abstract: Introduction: Medical student mental health and wellness has been an increasingly hot topic over the past decade. Much of the research, however, has remained focused more on anxiety and depression and less on other less common but just as detrimental mental health disorders such as PTSD, bipolar disorder, OCD and others. In addition to the more traditional psychological stresses medical students experience, they also experience physical consequences of their training, often with sleep patterns suffering most initially. Methods: The questionnaire consists of thirty-five questions, compromising of demographic questions, questions relating to USMLE exams and education, the STOP-Bang Questionnaire, Epworth Sleepiness Scale, Fatigue Severity Scale and PTSD DSM-V Questionnaire. This survey was sent out between March and April of 2020 and was distributed to all medical students and residents with an LSU Health Shreveport email address via RedCAP, an encrypted electronic survey tool. Results: A total of 78 participants responded to our survey, with 91.1% identifying as medical students and the rest as residents. 64.1%, identified as female, 34.6% identified as male and 1.3% declined to answer. While 43% of our participants found their educational experience emotionally traumatizing, 75% of them felt that preparing and/or taking USMLE exams was emotionally traumatizing. In regards the portions of our questionnaire that served as sleep disorder screening questions, the average score for the STOP-Bang was 1.48 (SD +/- 1.15) the average score for the ESS was 6.85 (SD +/- 4.72) and the average score for the FSS was 32.04 (SD +/- 11.99). It should be noted that, while the average score of the PTSD screening portion was 20.34 (SD +/- 17.47), 18 participants scored above 38, the minimum score needed to qualify for a PTSD diagnosis. Conclusion: These results suggest some correlations that warrant further future study. It is worrisome that while less than half of our participants stated their educational experience as harrowing, 75% stated preparing for and/or taking these required exams was emotionally traumatizing. The possible connections suggested here between USMLE exams and an increase in fatigue, lack of motivation and PTSD symptoms urge us to look more closely at the impact of the USMLE. Support (if any):